Exploring on Preference of Bulk Store’s Video - I-Ting Lee; Chun-Chih Chen; Jiann-Sheng Jiang (International Journal of Social Sciences and Artistic Innovations)
The green trend or sustainable consumption is gaining recognition nowadays. In that, the reduction of plastic waste is a key to the circular economy. Bulk stores incorporate a policy of zero food waste. In this study, we analyzed the experience of unpackaging using the Kano model. The relationship between the generation of video preferences was analyzed to promote circular stores and increase willingness to adopt sustainable consumption. Necessary qualities for sustainable consumption were also determined based on consumer feedback. Videos of bulk stores are important in promoting sustainable consumption. For sustainable development, the design of videos needs to be improved to increase the application of digital media in the advertisement and promotion of sustainable development.